Psychosocial issue among office workers: a case study at a Public Higher Education Institution in Malaysia - Ezrin Hani, Sukadarin; Norhidayah, Abdull; Junaidah, Zakaria; Abdullah, Ibrahim (Medwell Publications, 2016)
Self-awareness of workers’ own health status had been proven can prevent work-related harm and injury and also mental health problems. Both mental and physical health improvements (physical and psychosocial factors) should be the main focused in any research. Workload and work-related stress are the examples of psychosocial factors that may exist in each organization. A case study related to safety and health was conducted among staff at Human Resources Management Division (HRMD) at a public higher education institution (Institut Pengajian Tinggi Awam -IPTA) in Malaysia. Total numbers of 22 staff were employed. However, only 21 staffs were participated in this study which contributed to about 95% of the response rate. A set of self-administered questionnaires which consist of questions on socio demographics information, questions on working hour, questions on workload and also questions on work-related stress were used as the study instruments. Result shows that office workers in HRMD, work in long hours in a week to keep up with workload. The availability of supplies, equipment and materials to do the work however, helps the workers to manage their works in a proper way. The relationship of inter-staff also found in a good condition. This study will be useful for other researcher to conduct a psychosocial study among office workers in a bigger sample size. This finding also can be as a guidance to manage workload and work-related stress in workplace.